1996
DOI: 10.1159/000211420
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 and Drug Development for Skin Diseases

Abstract: Cytochromes P-450 (CYPs) are the most versatile and important class of drug-metabolizing enzymes which are induced in mammalian skin in response to xenobiotic exposure. CYPs are the target of special interest in the development of pharmaceuticals for skin diseases because most, if not all, drugs available in the armamentarium of the dermatologist are substrates, inducers or inhibitors of this enzyme family. The functional significance of drug metabolism in the skin and the implication of CYP in skin pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Several studies have demonstrated the inducibility of CYP1A1 and related mono-oxygenase activities in human skin, and in hair follicles, following the exposure to PAHs, b-naphtoflavones and glucocorticoids. 27 Data obtained in the present study confirmed the constitutive expression of this CYP mRNA in preparations of human epidermal keratinocytes, and in the resulting cultured keratinocytes, even after UV irradiation. The same observation was made about CYP3A5.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have demonstrated the inducibility of CYP1A1 and related mono-oxygenase activities in human skin, and in hair follicles, following the exposure to PAHs, b-naphtoflavones and glucocorticoids. 27 Data obtained in the present study confirmed the constitutive expression of this CYP mRNA in preparations of human epidermal keratinocytes, and in the resulting cultured keratinocytes, even after UV irradiation. The same observation was made about CYP3A5.…”
Section: Discussionsupporting
confidence: 85%
“…Thereby, the AhRR is thought to form a negative feedback loop on the AhR gene battery, including its own transcription. Such AhR signaling was found in almost all cells of the body, including skin (Das et al, 1986;Ahmad et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The role of PXR in the skin has been little investigated [213] even though the skin is an important xenobiotic metabolizing organ which expresses several PXR target genes [54,125,213,214,215]. Natural PXR ligands in the skin are not known, but could include progesterone and cholesterol, and their derivatives, bile acids, pregnanes and corticosterone [216,217,218,219,220,221].…”
Section: Xenobiotic Receptors and Atopic Dermatitismentioning
confidence: 99%